(untitled) (Journal of Contemporary Issues in Accounting, 2026)
This study examined the effect of firm characteristics on the sustainability reporting of listed conglomerate firms in Nigeria. The specific objectives were to determine the effect of firm size, firm leverage and firm profitability on sustainability reporting of listed conglomerate firms in Nigeria. Ex-post facto research design was used in the study. The population of the study comprised all the six (6) conglomerate firms listed on the Nigerian exchange group. Purposive sampling was used to select a sample size of five (5) firms. This study utilized secondary data from the annual reports of the sampled firms. The data collected spans from 2014 to 2023, being a ten-year period. Descriptive statistical analysis was carried out using mean, standard deviation, minimum, and maximum values. Hypothesis testing was done using robust least square regression analysis. The findings showed that: firm size had a significant positive effect on the sustainability reporting of listed conglomerate firms in Nigeria (β = 1.935897; p-value = 0.0402); firm leverage had a significant negative effect on the sustainability reporting of listed conglomerate firms in Nigeria (β = -4.734726; p-value = 0.0000); firm profitability had a positive but non-significant effect on the sustainability reporting of listed conglomerate firms in Nigeria (β = 1.099459; p-value = 0.4271). In conclusion, the study revealed that larger conglomerate firms in Nigeria were more likely to engage in sustainability reporting, firms with higher leverage were less likely to do so. The study recommended that senior management teams of conglomerate firms should allocate resources towards comprehensive sustainability reporting frameworks to further strengthen their commitments and transparency.